Church’s Authority and The Disappearence of God In George Bernard Shaw’s The Miraculous Revenge Short Story - Zumrotun Lutfiah (Sekolah Tinggi Agama Islam Kuningan, 2023)
This research tries to investigate and elaborate the intention of Shaw in writing such a hypocrite story which one side praise God, church and bible, but another side mostly portrayed the disappearance of God. Late Victorian is considered as the period which the presence of God is a must in every single activity that the Victorian done because of their purpose to back to the nature by considering God as the Holy creation through praising church. However, Shaw shows a big contradiction between the reality on the Victorian era with the elaboration of the short story by questioning the presence of God even though it looks like the story is about praising the church. This research is analyzed using qualitative descriptive method with historical approach and historicism theory. The result of this study indicates that church has the authority which is legitimate by the society even though the society itself has a doubt on the presence of God and even disappearing God in their life in society. Therefore, the power or the authority which is had by the church is not absolute and can be replaced by other beliefs because the reality which is faced by the society cannot always be understood by the church.